Nutrition and Lifestyle Interventions in the Management of COPD: A Comparative Review in Indian and European Health Care - Singh, Megha; Nehra, Shalu (Journal of Neonatal Surgery, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a debilitating respiratory disorder marked by persistent airflow limitation and chronic airway inflammation. Responsible for over 3.2 million deaths annually, COPD ranks as the third leading cause of mortality globally, with a disproportionately high impact on low- and middle-income countries such as India. While pharmacological management remains a cornerstone of treatment, non-pharmacological strategies—particularly those involving nutrition and lifestyle modifications—are increasingly recognized for their role in improving clinical outcomes and quality of life. This review critically examines and compares the implementation and effectiveness of nutrition and lifestyle-based interventions in the management of COPD within Indian and European healthcare systems. In European contexts, structured pulmonary rehabilitation programs, routine nutritional assessments, and integrated behavioral support services are well-established. Conversely, India faces systemic challenges, including socioeconomic disparities, infrastructural limitations, and a lack of culturally standardized care models. However, India also presents unique opportunities through the integration of traditional practices such as yoga, community-led healthcare delivery, and diverse regional diets. By identifying both region-specific barriers and successful strategies, this review underscores the urgent need to incorporate culturally sensitive, multidisciplinary, and policy-supported non-pharmacological interventions into mainstream COPD care. Strengthening such integrative approaches holds the potential to bridge healthcare gaps, enhance patient well-being, and reduce the global burden of COPD.